PENGARUH KEAKTIFAN BERORGANISASI DAN PEMANFAATAN JAM BELAJAR DI RUMAH TERHADAP PRESTASI BELAJAR - Andini, Thoifah Asri; ., Ngadiman; Ivada, Elvia (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe purposes of this research were to investigate (1) the influence of the activeness in organization on students learning achievements at Accounting Department of State Vocational High School of X in 2016/2017; (2) the influence of utilization hours home study on students learning achievements at Accounting Department of State Vocational High School of X in 2016/2017. This research used the quantitative research method with the causal relationship design. Its population was all of the students in Grade X and XI Accounting Department of State Vocational High School of X in 2016/2017. The samples of research were all of the students as many as 98 in Grade X and XI Accounting of the school and were determined by using the non-probability sampling with sampling saturated. Its data were collected through questionnaire used to obtain data about the activeness in organization and utilization of study hour at home, while the documentation used to collect data on average value of report cards of students The data were validated by using the Pearsonâs Product Moment at the significance level of 5%, and their reliability was tested by using the Cronbachâs Alpha formula. They were then analyzed by using the statistical, descriptive, and inferential model of analysis, namely: the multiple linear regression tests. The results concluded (1) there was a positive and significant influence between the activeness in organization on students learning achievements at Accounting Department of State Vocational High School of X in 2016/2017. It was shown from the calculations tcount > ttable (8,267 > 1,98525) at significance level 5% (0.000 < 0.05); (2) there was a positive and significant influence between the utilization hours home study on students learning achievements at Accounting Department of State Vocational High School of X in 2016/2017. It was shown from the calculations tcount > ttable (5,527 > 1,98525) at significance level 5%Keywords: The Activeness in Organization, Utilization Hours Home Study, Learning AchievementsABSTRAKTujuan penelitian ini adalah untuk mengetahui (1) pengaruh keaktifan berorganisasi terhadap prestasi belajar siswa Jurusan Akuntansi di SMK X tahun ajaran 2016/2017; (2) pengaruh pemanfaatan jam belajar di rumah terhadap prestasi belajar siswa Jurusan Akuntansi di SMK X tahun ajaran 2016/2017. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian hubungan kausal. Populasi penelitian ini adalah siswa kelas X dan XI Jurusan Akuntansi di SMK X. Sampel penelitian adalah seluruh siswa kelas X dan XI Jurusan Akuntansi di SMK X yang berjumlah 98 siswa yang ditentukan menggunakan teknik non-probability sampling jenis sampling jenuh. Angket dan dokumentasi digunakan sebagai alat pengumpulan data. Teknik analisis data menggunakan statistik deskriptif dan inferensial meliputi uji regresi linear berganda. Hasil penelitian menyimpulkan (1) terdapat pengaruh positif dan signifikan keaktifan berorganisasi terhadap prestasi belajar siswa Jurusan Akuntansi di SMK X tahun ajaran 2016/2017 dengan hasil thitung > ttabel (8,267 > 1,98525) pada taraf signifikansi 5% (0,000 < 0,05); (2) terdapat pengaruh positif dan signifikan pemanfaatan jam belajar di rumah terhadap prestasi belajar siswa Jurusan Akuntansi di SMK X tahun ajaran 2016/2017 dengan hasil thitung > ttabel (5,527 > 1,98525) pada taraf signifikansi 5% (0,000 < 0,05).Kata Kunci: Keaktifan Berorganisasi, Pemanfaatan Jam Belajar di Rumah, Prestasi Belajar